Immunosuppressants Tacrolimus and Sirolimus revert the cardiac antifibrotic properties of p38-MAPK inhibition in 3D-multicellular human iPSC-heart organoids - Tian, Yu; Tsujisaka, Yuta; Li, Vanessa Y.; Tani, Kanae; Lucena-Cacace, Antonio; Yoshida, Yoshinori (Frontiers in Cell and Developmental Biology, 2022)
Cardiac reactive fibrosis is a fibroblast-derived maladaptive process to tissue injury that exacerbates an uncontrolled deposition of large amounts of extracellular matrix (ECM) around cardiomyocytes and vascular cells, being recognized as a pathological entity of morbidity and mortality. Cardiac fibrosis is partially controlled through the sustained activation of TGF-β1 through IL-11 in fibroblasts. Yet, preclinical studies on fibrosis treatment require human physiological approaches due to the multicellular crosstalk between cells and tissues in the heart. Here, we leveraged an iPSC-derived multi-lineage human heart organoid (hHO) platform composed of different cardiac cell types to set the basis of a preclinical model for evaluating drug cardiotoxicity and assessing cardiac fibrosis phenotypes. We found that the inhibition of the p38-MAPK pathway significantly reduces COL1A1 depositions. Yet, concomitant treatment with organ-rejection immunosuppressant drugs Tacrolimus or Sirolimus reverts this effect, opening new questions on the clinical considerations of combined therapies in reducing fibrosis after organ transplantation.